PERENCANAAN LANSKAP CIGUDEG SEBAGAI IBU KOTA KABUPATEN BOGOR BARAT - Hasanah, Nur Hepsanti; Pramukanto, Qodarian (http://arl-faperta.ipb.ac.id/, 2016)
West Bogor region is a new autonomous region as an expansion of the Bogor Region. The Establishment of a new autonomous region was approved in 2014 and it is one step to catalyze regional development that previously hindered because the area is too large. Cigudeg subdistrict designated as the capital city of West Bogor region, followed by a few supporters in the surrounding area that serves as a center of commercial and administration zone. The purpose of this study was to make Cigudeg landscape planning using METLAND (The Metropolitan Landscape Planning Model Study) by Fabos. This method is based on analysis of critical resources, landscape hazards and physical development suitability. The result of this research is landscape plan of Cigudeg.